Information science the basics - Pintar, Judith; Hopping, David (The basics, 2023)
Information Science: The Basics provides an accessible introduction to the multifaceted field of Information Science (IS). Inviting readers to explore a modern field of study with deep historical foundations, the book begins by considering the complexities of the term 'information.' Each chapter surveys a different area within IS, surveying its history, technologies, and practices with a critical eye. This interdisciplinary field incorporates a wide range of approaches which it shares with humanities, social science, and technology fields, all of which are introduced to the reader. What makes this volume unique is its emphasis on the connections between information, technology, and society. The need to share information more effectively in response to social, environmental, and biomedical challenges has never been so urgent, but there are risks as well as benefits that come with the emerging technologies that make it possible, which are discussed in the volume. The book also explores how IS, with its long-standing attention to intellectual freedom and digital inclusion, and a deep commitment to the protection of privacy, data ethics, and algorithmic transparency, can contribute to the creation of a more open and equitable society. Information Science: The Basics is essential reading for anyone who wishes to know more about information and the impact it has on our world. It will be particularly useful for anyone intending to study IS at the undergraduate level or considering a shift to a career in the information professions"--